Innovation and Productivity in Services: Evidence from Germany, Ireland and the United Kingdom - Bettina Peters; Rebecca Riley; Iulia Siedschlag; Priit Vahter; John McQuinn (European Commission, Joint Research Centre (JRC), 2014)
This paper examines the links between innovation and productivity in service enterprises. For this purpose, we use micro data from the Community Innovation Survey 2008 in Germany, Ireland and the United Kingdom, and estimate an augmented structural model. Our results indicate that innovation in service enterprises is linked to higher productivity. In all three countries analysed, among the innovation types that we consider, the strongest link between innovation and productivity was found for marketing innovations. Our empirical evidence highlights the importance of internationalisation in the context of innovation outputs in all three countries. The determinants of innovation in service enterprises appear remarkably similar to the determinants of innovation in manufacturing enterprises.
Keywords: F61; L25; O31; 330; Internationalisation of services; innovation; productivity